Update on autoimmune dermatoses in canines characterized by pustules, vesicles and blisters: anatomopathology and diagnosis - Sieben, Cintia (2019)
The aim of this revision was to update the clinical, histopathological and pathogenic aspects of autoimmune dermatoses that affect canines and that are characterized by pustules, vesicles and blisters as the primary lesion. The clinical aspects and the histopathological features of the diseases that are part of the pemphigus complex and the autoimmune subepidermal bullous diseases are considered. In addition, immunological techniques used in the diagnosis and characterization of this group of diseases are described.